Preschool-aged children 24-hour movement behaviours before and during COVID-19 - Mingming Cui; Xiaojuan Wang; Zhaoxu Lu; Anthony D. Okely; Katharina Kariippanon; Ellie K. Taylor; Ting Zhang; Hongyan Guan (Sports Medicine and Health Science)
The coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) affected health, economies, and lifestyles, but little is known about its impact on children. We aimed to investigate changes in 24-hour (h) movement behaviours of pre-school children before and during COVID-19, and factors that influenced these. Children aged 3–6 years were recruited in Beijing in 2019, and their movement behaviours over 24 ​h assessed by questionnaire, as part of the International Study of Movement Behaviors in the Early Years (SUNRISE) study. We conducted the survey again during COVID-19, and compared the children’s movement behaviours before and during COVID-19 and associated factors. Overall, 196 parents completed the survey at both time points. The percentage of children meeting movement guidelines decreased during the pandemic (p ​< ​0.01). Total physical activity decreased less among children getting good quality sleep or with more adults in the household (p ​< ​0.01). Children who were not cared for primarily by their mother had a greater decrease in moderate to vigorous intensity physical activity (p ​= ​0.02), but the decrease was smaller among children whose parents used the internet to support their physical activity and/or screen time (p ​< ​0.05). Children who used electronic screen devices in the 2 ​h before bedtime or whose parents reported body temperature in webchats had a greater increase in sedentary screen time (p ​< ​0.05). Children spending more time outdoors showed a smaller decrease in sleep (p ​< ​0.01). Overall, children’s movement behaviours changed significantly during the pandemic.